Juridical Analysis of Hospital Liability for Actions of Doctors Performing Medical Malpractice - Budiman, Arief; Rizka, Rizka; Absori, Absori (Universitas Katolik Soegijapranata Semarang, 2023)
Legally the Hospital has responsibility for the negligence committed by its health workers. The responsibility for criminal acts of malpractice is currently in the spotlight because the legal rules governing it are still unclear. This is because the regulations regarding the qualifications for malpractice are not clearly stated in the legal rules. The purpose of this research is to analyze the responsibility of the hospital for the actions of doctors who commit malpractice. Using a normative juridical method with a statute approach, namely examining all laws and regulations related to the issues to be discussed. The results of the analysis show that based on Law No. 44 of 2009 concerning Hospitals, hospitals have a responsibility if their medical members are proven to have committed negligence. Until now, Indonesia does not have a law that implicitly regulates medical malpractice.